DAMPAK PENERAPAN AUDIT MANAJEMEN ATAS FUNGSI SUMBER DAYA MANUSIA PADA KOPERTIS WILAYAH VII - Susriyati, Susriyati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to find out the impact of the management audit implementation on HRD at Kopertis Wilayah VII. The Human resources (HRD) audit is an evaluation and comprehension analysis to the HRD program. SDM audit focuses on the evaluation to the organization activity. The result of HRD audit will find out whether the HRD potential in an organization is already fulfilled or not. Through analysis and recommendation, it can increase the performance of HRD program at Kopertis Wilayah VII. The research result shows that the implementation of management audit of HRD function is already effective. The regulation and policy at Kopertis Wilayah VII is in according to the Government regolation. Each of the program which are implemented by Kopertis Wilayah VII is according to the regulation an Government policy. Those kinds programs are: employessâ planning has been implemented according to DUK (list of ranks in order) and well documented. Employeesârecruitment and selection has been implemented according to procedure which is in proposing formation by the implementer secretary through subsection staffing. The performance evaluation is already according to government regulation No. 10 year 1979 which is DP3 (the list of job evaluation). Salary employeesâ policy use BNI to disburse employeesâ salary. Safety and health program of employeesâ is in according to government program by using ASKES (health insurance). The implementation of management audit on the HRD function in effective, efficient and economic can increase the performance at Kopertis Wilayah VII.Keywords: HRD Planning, Selection and Recruitment, Performance Evaluation, Salary Policy, Employeesâ Safety and Health.